2022
DOI: 10.1177/20436106221117844
|View full text |Cite
|
Sign up to set email alerts
|

Thinking time: Producing time and toddler’s time to think in ECEC

Abstract: Toddlers contribute to early childhood education and care (ECEC) environments in unique ways in contrast to older children and adults. In this article, we explore early childhood teachers’ stories about toddlers, thinking, and time. We follow a moment with a toddler’s story told with his fingers, and discuss it through teachers’ stories. Our focus is on what ideas about toddlers, time, and thinking these stories produce, and how these ideas affect toddler’s possibilities to contribute to daily life in ECEC. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…This respects the competence and capability of young children to make choices and express their views, which are listened, respected and acted on by adults. Here the actions of practitioners align with Moxnes and Aslanian's (2022) findings that adult's engagement with toddler's thinking time opens up new possibilities for relationships in the early childhood setting but also disrupts assumptions about how children might choose to organise their time.…”
Section: Vignette 4 Children's Choices In a Highscope Settingmentioning
confidence: 68%
See 2 more Smart Citations
“…This respects the competence and capability of young children to make choices and express their views, which are listened, respected and acted on by adults. Here the actions of practitioners align with Moxnes and Aslanian's (2022) findings that adult's engagement with toddler's thinking time opens up new possibilities for relationships in the early childhood setting but also disrupts assumptions about how children might choose to organise their time.…”
Section: Vignette 4 Children's Choices In a Highscope Settingmentioning
confidence: 68%
“…By developing an 'unhurried presence'(p. 33) in the early childhood setting adults were able to realise caring values and in turn provide opportunities for children to exercise citizenship. Similarly, Moxnes and Aslanian's (2022) study in Kindergartens in Norway, considered how young children's ability to enact agency is affected by their teachers' perceptions of toddler's thinking. They found that 'toddler's thinking inspired moments of diffraction and deep thinking '(p. 285) in the Kindergarten that disrupted habitual beliefs in early childhood practice about time, its link to efficiency and assumptions of linear thinking.…”
Section: Nurturing Citizenship In Early Childhood Practice -The Role ...mentioning
confidence: 99%
See 1 more Smart Citation